Advocacia Pública Municipal: atividades de advogados públicos nos municípios como privativas de servidores públicos efetivos - Vieira, Raphael Diógenes Serafim (2023)
The exercise of the attributions of public advocacy as exclusive to public servants holding effective positions in the Municipalities is the subject of this work. Nevertheless, it protected the thesis of private attribution of the exercise of this competence for the career server previously concurred by the Public Advocacy of the Union, the States and the Federal District, on the other hand, for several reasons that are scrutinized in this study, pending theoretical divergences the Application of this same relationship to exist at the municipal level. The main legal and meta-legal arguments appreciated by the doctrine and jurisprudence for the examination of the subject are: (i) the gap in the prediction of the municipal prosecutor's career and the Municipal Public Advocacy body in Section II of Chapter IV of the Federal Constitution of 1988; and (ii) the alleged higher economic cost of an effective lawyer in comparison with other categories of public agents who, under the factual prism, could be imbued with the same plex of tasks. It turns out that the misunderstanding of a portion of the doctrine and jurisprudence on the legal issue has led not only to mistaken scientific studies, but, in addition, it provides an environment of legal authorization conniving with a framework of institutional precariousness in the Municipalities regarding the exercise of this office, since the theoretical constructions in the world of duty will largely determine the configuration of the world of being, verbi gratia: (i) the verification of, at least, five categories of public agents, under different legal regimes, who have provided Public Advocacy skills in the Municipalities; and (ii) the maintenance of a deficit of effective lawyers, as two thirds of these entities are not protected by a single public lawyer, according to research published in the 1st National Diagnosis of Municipal Public Advocacy in Brazil, which statistically confirmed an empirical deduction which, until then, was intuitive. To face the problem and prove the hypothesis of the work, the attributions of public lawyers were examined, the institutional purposes of these attributions, as well as the taxonomy of existing legal regimes for public agents, with the purpose of, from the comparisons, establish the exact association between the type of public function exercised and the type of legal regime able to provide the public agent with the necessary institutional protections to fulfill his function. After developing the legal foundations that support the proposed thesis and, at the same time, deconstructing the arguments that support it, presenting, with scientific rigor based on the methods employed, the kind of correct legal regime to arm the public agent entrusted with the practice of law public guarantees necessary for the survival and preservation of political neutrality in the performance of this public function, which is the statutory regime proper to the charge of effective provision. The study is concerned with presenting a theoretical construction that is epistemologically correct, and, for that, that can contribute to the maximum transfer of the Constitution, to the strengthening of the Democratic State of Law and, finally, to the fight against corruption